Leadership types and whistleblowing intention in public sector: the mediation role of justice - Ilham Maulana Saud; Ietje Nazaruddin; Arif Wahyu Nur Kholid (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study examines the effect of two leadership types, ethical leadership (EL) and servant leadership (SL), on whistleblowing intentions with three justice dimensions: distributive, interactional, and procedural, as mediators.Design/Methodology/Approach: This research involved local government organizations (LGO) employees in several regencies in Indonesia, including Purworejo, Sumbawa, Pelalawan Riau, the Special Region of Yogyakarta, and Surakarta. The hypotheses were tested using the SEM-PLS technique.Research findings: The results discovered that EL positively affected whistleblowing intention directly and through (mediated) procedural and interactional justice. Meanwhile, SL did not directly affect whistleblowing intention, yet it could affect it when mediated by procedural justice. Furthermore, distributive justice could not mediate the relationship between either SL or EL on whistleblowing.Theoretical contribution/Originality: The novelty of the research is to explore and comprehensively analyze how a leadership style can influence someone to do whistleblowing in the government sector by paying attention to the crucial role of the justice dimension. The results of this study provide valuable insights for the government to increase employee motivation in whistleblowing.Practitioner/Policy implication: Drawing from this insight, the leader of the LGOs must have the characteristic of EL since it can facilitate and motivate employees to blow the whistle when they find fraud in the organization. In addition, a leader with EL can create fairness in the organization. Thus, EL not only can affect employees to blow the whistle but also can raise the three-dimensionality of justice in the organization.Research limitation/Implication: The implementation of leadership, either SL or EL, in the context of the public sector, whose primary purpose is to enhance government accountability, particularly in emerging countries, is still lacking. Moreover, the process underlying how leadership affects whistleblowing still holds critical gaps, particularly issues related to leadership dynamics.